Market Relations and the Competitive Process - John S. Metcalfe; Alan Warde (Manchester University Press, 2003)
There has been increasing interest and debate in recent years on the instituted nature of economic processes in general and the related ideas of the market, in particular the competitive process. This debate lies at the interface between two largely independent disciplines, economics and sociology, and reflects an attempt to bring the two fields of discourse more closely together. This book explores this interface in a number of ways, looking at the competitive process and market relations from a number of different perspectives. It includes a wide range of contributors, most of whom are leading writers and thinkers in the field. The book considers the social role of economic institutions in society and examines the various meanings embedded in the word 'markets', as well as developing arguments on the nature of competition as an instituted economic process, rather than as competition being something that disturbs norms or institutions. It goes on to consider the deeper and more involved connection between markets and cognition, explaining how institutions can ease cognitive difficulties, and the effect of culture on markets and competition is also fully studied. This book will be of vital use to students and academics working in the fields of economics, sociology and business studies. It sketches the agenda for future research about markets and the competitive process.
Keywords: 330; economics; consumerism; marketing; Wettbewerb; Marktmechanismus; Wirtschaftssoziologie